Pemeriksaan Gangguan Keseimbangan pada Usia Produktif dengan Menggunakan Fukuda Stepping di Dinas Lingkungan dan Kehutanan Yogyakarta - Ni Luh Diah Windayani; Dimas Sondang Irawan; Fernia Julantika (Vitamin : Jurnal ilmu Kesehatan Umum, 2024)
Balance limitations pose a significant concern for individuals of productive age. Productive age people who work in offices tend to have less physical activity. Lack of physical activity can affect the decrease in muscle strength, joints which results in a decrease in motion, steps tend to be short, feet cannot tread firmly and are easily unsteady. The decrease in motion function causes balance problems. If this continues to be allowed, it will cause the risk of falls and a decrease in the quality of life of workers in productive age. So it is important for office workers, especially workers at the Yogyakarta Environment and Forestry Service, to understand the importance of maintaining balance. One of the tests that can be used to assess balance is the Fukuda stepping test. This examination is carried out with the Fukuda test and vital sign checks to find out that this test is safe to be carried out by participants. The number of participants in this activity was 27 people consisting of men and women of productive age. This activity was held on Friday, October 13, 2023 at the Yogyakarta Environment and Forestry Service. After this test was carried out, it was found that 23 out of 27 office workers of productive age had balance disorders. After this test, the participants became more aware of the importance of maintaining balance and how to maintain it.